Antibiotic Elution from Cement Spacers and Its Influencing Factors - Bernd Fink; Kevin D. Tetsworth (Antibiotics)
Antibiotic-loaded cement spacers play a crucial role in two-stage revision arthroplasty of infected total hip and knee prostheses. There is still controversy regarding whether the elution from antibiotic-loaded cement spacers is greater than the MIC for a prolonged time between stages. Therefore, the aim of the current review was to determine how long spacers elute antibiotics above the MIC for most causative microorganisms, as well as to evaluate what factors influence that elution. Independent of methodological differences and weaknesses of the studies themselves, several study results indicate that after an early peak of antibiotic release from the spacer in the first 1 to 2 days (followed by a gradual decline), a sufficient release above the MIC for most causative bacteria continues for 6 to 12 weeks.